ПОНЯТТЯ ТА СУТНІСТЬ ШЛЮБНОГО ДОГОВОРУ В УКРАЇНІ - Єніна, Лариса Вікторівна (SUPREMANCE OF LAW, 2018)
The article deals with scientific approaches to the definition of the concept and essence of marriage contract. The necessity of its consolidation in the legislation of Ukraine is substantiated. Based on scientific research and legislation, the main features of the marriage contract are identified. Proposed author concept “marriage contract”.
Keywords: contract; spouses; marriage; property relations; marriage contract; rights and duties of spouses